Organophosphate and organochlorine resistance in larval stage of aedes albopictus (Diptera: Culicidae) in Sabah, Malaysia - Elia-Amira, Nur Mohd Roslin; Chen, Chee Dhang; Lau, Koon Weng; Lee, Han Lim; Low, Van Lun; Norma-Rashid, Yusoff; Sofian-Azirun, Mohd (Oxford University Press, 2010)
The present study aims to investigate the susceptibility status of Aedes albopictus (Skuse) collected from residential areas in Sabah, Malaysia towards eight WHO-recommended dosages of larvicides representing the classes of organophosphates and organochlorines. Field and reference strains of Ae. albopictus larvae were bioassayed in accordance to WHO standard methods using diagnostic dosages of bromophos, malathion, fenthion, fenitrothion, temephos, chlorpyrifos, dichlorodiphenyltrichloroethane (DDT), and dieldrin. The results revealed that Ae. albopictus was resistant (mortality < 90%) towards malathion, temephos, and DDT. In addition, most of the Ae. albopictus strains exhibited a wide range of susceptibilities against bromophos, with mortality ranged from 49.33 to 93.33%. On the contrary, only dieldrin was able to induce 100% mortality against all strains of Ae. albopictus. Tolerance to fenitrothion, fenthion, and chlorpyrifos, with mortality ranging from 81.33 to 97.33%, was also observed in this study.